2018
DOI: 10.1002/hbm.24492
|View full text |Cite
|
Sign up to set email alerts
|

ROI and phobias: The effect of ROI approach on an ALE meta‐analysis of specific phobias

Abstract: About 90% of fMRI findings on specific phobias (SP) include analysis of region of interest (ROI). This approach characterized by higher sensitivity may produce inflated results, particularly when findings are aggregated in meta‐analytic maps. Here, we conducted a systematic review and activation likelihood estimation (ALE) meta‐analysis on SP, testing the impact of the inclusion of ROI‐based studies. ALE meta‐analyses were carried out either including ROI‐based results or focusing on whole‐brain voxelwise stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 63 publications
2
30
0
Order By: Relevance
“…laboratory-acquired fear), where imaginal and in vivo extinction appear to involve overlapping neural circuity [23], and partly extend such findings to naturally occurring phobic fear. Our results of increased activity in insula and cingulate cortex during phobic imagery are consistent with studies of specific phobia [18,20], scriptdriven-imagery studies of PTSD (e.g. [21]), and also neural activity observed in healthy individuals during mental imagery of emotional pictures [42].…”
Section: (A) the Neural Basis Of Imaginal Exposuresupporting
confidence: 90%
See 1 more Smart Citation
“…laboratory-acquired fear), where imaginal and in vivo extinction appear to involve overlapping neural circuity [23], and partly extend such findings to naturally occurring phobic fear. Our results of increased activity in insula and cingulate cortex during phobic imagery are consistent with studies of specific phobia [18,20], scriptdriven-imagery studies of PTSD (e.g. [21]), and also neural activity observed in healthy individuals during mental imagery of emotional pictures [42].…”
Section: (A) the Neural Basis Of Imaginal Exposuresupporting
confidence: 90%
“…Metaanalyses of these studies report consistent activations in fear processing areas, such as the amygdala, the insular cortex, the anterior cingulate cortex (ACC) and the anterior midcingulate cortex (MCC) [18,20]. Compared with healthy participants, phobic individuals show hyperactivation of the thalamus, cerebellum and the inferior frontal gyrus during perception of phobic stimuli [18,20]. In addition, some brain-imaging studies of PTSD have used script-driven mental imagery of trauma as symptom provocation.…”
Section: (B) Current Knowledge Of the Neural Basis Of Imaginal Exposurementioning
confidence: 99%
“…Emotional responses were associated with activations of the amygdalae 50,51 , while effective emotional regulation strategies reduce amygdala reactivity 52,53 . Furthermore, anxiety disorders and mood disorders 23,[54][55][56][57][58] are characterized by amygdala hyperreactivity, normalized by effective pharmacological and psychological treatments 59,60 . Thus, our results support the role of amygdala dysfunction as a transdiagnostic mechanism, present in BPD, similarly to other disorders.…”
Section: Convergence Of Differencesmentioning
confidence: 99%
“…Furthermore, theoretical grounding of the a priori ROI selection may be problematic. For instance, in a meta-analysis on specific phobias, we showed that only 19 out of 31 studies explicitly justified the choice of ROI based on previous literature (Gentili et al, 2019). Frequently, the rationale supporting ROI selection is based on vague statements or on citing previous findings without motivating how these suggest an association between a well-defined brain area and a specific mental process.…”
mentioning
confidence: 98%
“…This method is ubiquitous in the fMRI literature (Poldrack, 2007). For instance, in an Activation Likelihood Meta-Analysis on specific phobia, we found that 28 out of 31 papers employed ROI approaches (Gentili, Messerotti Benvenuti, Lettieri, Costa, & Cecchetti, 2019). In principle, ROI analysis can be statistically appropriate and useful when the target brain region is defined a priori.…”
mentioning
confidence: 99%